Synthesis and characterization of azoxy based mesogenic diols - Mulani, Khudbudin Baban; Ganjave, Nitin V.; Chavan, Nayaku (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Azoxy based rigid mesogenic diols have been synthesized using two steps. Phenol/cresol is used as starting material. Synthesized diols are characterized by IR, H-1 and C-13 NMR, and mass spectroscopic methods. Thermal properties have been determined by thermo gravimetric analysis method and crystallinity patterns have been obtained by wide angle X-ray diffiactogram. Substituted phenol (methyl) is used to study the effect of substitution on physical and thermal properties of rigid azoxy mesogenic diol. The detailed characterization of azoxy based rigid diols is reported in this communication, which is highly useful for fundamental and applied research, particularly in liquid crystals and liquid crystalline polymers. The experimental results reveal that phenol based rigid mesogenic diols have high thermal stability and degree of crystallinity than methyl substituted rigid mesogenic diols.
Keywords: Azoxy; degree of crystallinity; diol; mesogen; phenol; thermal stability

C-O hydrogenolysis of C3-C4 polyols selectively to terminal diols over Pt/W/SBA-15 catalysts - Bhowmik, Susmita; Enjamuri, Nagasuresh; Marimuthu, Banu; Darbha, Srinivas (Catalysts, 2022)
Pt/W/SBA-15 catalysts (with Pt-loading = 0.5-4 wt% and W-loading = 1 wt%) prepared by the sequential impregnation method were evaluated for selective C-O cleavage of erythritol and glycerol in an aqueous medium. The Pt and W particles dispersed on SBA-15 approached close proximity at higher Pt loadings and afforded synergistic enhancement in C-O hydrogenolysis activity/selectivity. 1,4-Butanediol yields of 30.9% (at 190 degrees C, 50 bar H-2 and 24 h) and 1,3-propanediol yields of 34.4% (at 190 degrees C, 50 bar H-2 and 12 h of reaction) were obtained over these catalysts. Pt nanoparticles (facilitating dissociative H-2 adsorption and spillover) and W (present as acidic oligomeric WOx species; activating and coordinating the polyol via 1 degrees-OH group) worked in tandem for the selective hydrogenolysis of polyols yielding terminal diols of industrial demand.
Keywords: diol; Erythritol; Glycerol; Hydrodeoxygenation; Pt; SBA-15; W